Physical fitness mediates the inverse association between fatness indicators and academic achievement, despite the school vulnerability of adolescents—The Cogni-Action Project - Gajardo-Araya, Guillermo; Hernández-Jaña, Sam; Olivares-Arancibia, Jorge; Ferrari, Gerson; Delgado-Floody, Pedro; Cristi-Montero, Carlos (Frontiers in Nutrition, 2022)
Objective This study aims to determine the mediating role of physical fitness in the relationship between fatness indicators and academic achievement, exploring the influence of school vulnerability. Methods A total of 1,296 Chilean adolescents (aged 10 to 14 years; 50% girls) participated in this study. The global fitness score (GFS) was obtained by adding the three main components of the ALPHA fitness test: cardiorespiratory fitness (CRF), muscular fitness (MF), and speed/agility fitness (SAF). CRF was evaluated through the 20 m shuttle run test; MF by upper and lower limb strength tests; and SAF by the 4 × 10 shuttle run test. BMIz and WHtR were evaluated as general (unspecific) and central (specific) fatness indicators. Academic achievement was established through grades in math, language, and science and their average scores. Multiple mediation analyses were performed according to two models, adjusted for sex, maturity, and schools (model 1), and in model 2, the school vulnerability index (SVI) was added. The SVI is an important proxy of socioeconomic status at the school level, and it was categorized as high-, mid-, or low-SVI. Mediation percentages were calculated, and confidence intervals (bootstrapping) were used to establish significant findings. Results CRF, SAF, and GFS mediate the relationship between fatness indicators and academic achievement, both partially and totally (ranging from 12.7 to 59.2%). However, MF did not show any mediation effect. After controlling for SVI, CRF, and GFS, mediation changed from partial to total in the associations between math and science with WHtR. Although SAF contributed to GFS mediation, CRF seems to have the most significant mediation role for all academic achievements, regardless of SVI and the fat indicator studied. Conclusion A higher level of general physical fitness, especially CRF, significantly mediates the detrimental influence of fatness on the academic achievement of schoolchildren. This study suggests that physical fitness plays a relevant role in academic and public health, considering the high prevalence and detrimental influence of obesity and school vulnerability in children and adolescents.